Autoantibody status and histological variables influence biochemical response to treatment and long‐term outcomes in Japanese patients with primary biliary cirrhosis. Issue 8 (11th December 2014) - Nakamura, Minoru; Kondo, Hisayoshi; Tanaka, Atsushi; Komori, Atsumasa; Ito, Masahiro; Yamamoto, Kazuhide; Ohira, Hiromasa; Zeniya, Mikio; Hashimoto, Etsuko; Honda, Masao; Kaneko, Shuichi; Ueno, Yoshiyuki; et al.
<x xml:space="preserve">Abstract</x> Aim The aim of the present study is to evaluate the factors influencing biochemical response to treatment and the value of biochemical response for predicting long‐term outcomes in Japanese patients with primary biliary cirrhosis (PBC). Methods Biochemical response to ursodeoxycholic acid (UDCA) or UDCA plus bezafibrate was defined as good (≤upper limit of normal [ULN]), fair (≤1.5 × ULN) or poor (>1.5 × ULN) at 2 years after initiation of UDCA treatment. Associations between various factors (including age, sex, autoantibody status and histological variables at baseline), biochemical response to treatment and long‐term outcomes were evaluated in 164 Japanese PBC patients. Results Anti‐gp210 positivity and a higher bile duct loss score were significant risk factors for worse alkaline phosphatase (ALP) response (odds ratios [OR], 2.78 and 1.85, respectively). Age, anti‐gp210 positivity and anticentromere positivity were significant risk factors for worse alanine aminotransferase (ALT) response (OR, 1.05, 4.0 and 2.77, respectively). Anti‐gp210 positivity and a higher hepatitis score were significant risk factors for worse immunoglobulin (Ig)M response (OR, 2.10 and 2.06, respectively). Worse ALP and IgM response were significant risk factors for progression to late‐stage disease without jaundice (OR, 2.27 and 2.32, respectively). Worse ALT response was a significant risk factor for progression to late‐stage disease with persistent jaundice (OR, 11.11). Conclusion Biochemical response to treatment at 2 years, which is influenced by autoantibody status and histological variables at baseline, can predict long‐term outcomes in Japanese patients with PBC.